Giardial lipid rafts share virulence factors with secreted vesicles and participate in parasitic infection in mice - Grajeda, Brian I.; De Chatterjee, Atasi; Villalobos, Carmen M.; Pence, Breanna C.; Ellis, Cameron C.; Enriquez, Vanessa; Roy, Sourav; Roychowdhury, Sukla; Neumann, Aaron K.; Almeida, Igor C.; Patterson, Steven E.; Das, Siddhartha (Frontiers in Cellular and Infection Microbiology, 2022)
Giardia lamblia, a protozoan parasite, is a major cause of waterborne infection, worldwide. While the trophozoite form of this parasite induces pathological symptoms in the gut, the cyst form transmits the infection. Since Giardia is a noninvasive parasite, the actual mechanism by which it causes disease remains elusive. We have previously reported that Giardia assembles cholesterol and GM1 glycosphingolipid-enriched lipid rafts (LRs) that participate in encystation and cyst production. To further delineate the role of LRs in pathogenesis, we isolated LRs from Giardia and subjected them to proteomic analysis. Various cellular proteins including potential virulence factors—e.g., giardins, variant surface proteins, arginine deaminases, elongation factors, ornithine carbomyltransferases, and high cysteine-rich membrane proteins—were found to be present in LRs. Since Giardia secretes virulence factors encapsulated in extracellular vesicles (EVs) that induce proinflammatory responses in hosts, EVs released by the parasite were isolated and subjected to nanoparticle tracking and proteomic analysis. Two types of EV—i.e., small vesicles (SVs; <100 nm, exosome-like particles) and large vesicles (LVs; 100–400 nm, microvesicle-like particles)—were identified and found to contain a diverse group of proteins including above potential virulence factors. Although pretreatment of the parasite with two giardial lipid raft (gLR) disruptors, nystatin (27 μM) and oseltamivir (20 μM), altered the expression profiles of virulence factors in LVs and SVs, the effects were more robust in the case of SVs. To examine the potential role of rafts and vesicles in pathogenicity, Giardia-infected mice were treated with oseltamivir (1.5 and 3.0 mg/kg), and the shedding of cysts were monitored. We observed that this drug significantly reduced the parasite load in mice. Taken together, our results suggest that virulence factors partitioning in gLRs, released into the extracellular milieu via SVs and LVs, participate in spread of giardiasis and could be targeted for future drug development.